An Integrated Approach to Characterize Intestinal Metabolites of Four Phenylethanoid Glycosides and Intestinal Microbe-Mediated Antioxidant Activity Evaluation In Vitro Using UHPLC-Q-Exactive High-Resolution Mass Spectrometry and a 1,1-Diphenyl-2-picrylhydrazyl-Based Assay - Wang, Xiaoming; Chang, Xiaoyan; Luo, Xiaomei; Su, Meifeng; Xu, Rong; Chen, Jun; Ding, Yi; Shi, Yue (Frontiers in Pharmacology, 2019)
Intestinal bacteria play significant roles in metabolisms and pharmacological actions of active ingredients of traditional Chinese medicines. Phenylethanoid glycosides (PhGs) as typical phenolic natural products, possess wide bioactivities but low oral bioavailability. The aim of this work was to reveal metabolism mechanism of PhGs in intestinal tract and screening for more active metabolites. In this study, a rapid and reliable method using a effective post-acquisition approach based on the advanced ultra-high performance liquid-chromatography (UHPLC) coupled with hybrid Quadrupole-Orbitrap high resolution mass spectrometry (Q-Exactive-HRMS) providing full MS and HCD MS2 data and Thermo Scientific™ Compound Discoverer™ software with Fragment Ion Search (FISh) function in one single workflow was developed to investigate the instestinal microbial metabolisms of four typical PhGs. Furthermore, combined with a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, antioxidant activity evaluations on PhGs and their ralated metabolites had been simultaneously carried out to understand how instestinal microbiota transformations modulate their biological activity and explored in structure−activity relationships (SAR). As a result, 26 metabolites of poliumoside, 42 metabolites of Echinacoside, 42 metabolites of tubuloside A and 46 metabolites of 2’-acetylacteoside were identified, respectively. Degradation, reduction, hydroxylation, acetylation, hydration, methylation and sulfate conjugation were the major metabolic pathways of PhGs. Furthermore, the degraded metabolites with better bioavailable had potent antioxidant activity could be attributed to the phenolic hydroxyl groups. These findings would enhance understanding of the metabolism, pharmacological actions and real active forms of PhGs.